2009
DOI: 10.3892/etm_0000027
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of mild temperature hyperthermia combined with hexamethylenetetramine compared to its effect combined with tirapazamine in the treatment of solid tumors

Abstract: Abstract. this study aimed to assess the effect on solid tumors of mild temperature hyperthermia (mth) combined with hexamethylenetetramine (hmta) or tirapazamine (tpZ). Squamous cell carcinoma (Scc Vii) tumor-bearing mice were continuously administered 5-bromo-2'-deoxyuridine (Brdu) to label intratumor proliferating (p) cells. mice received hmta or tpZ through intraperitoneal single or subcutaneous continuous administration, with or without MTH (40˚C, 60 min), followed or not by γ-ray irradiation or cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In squamous cell carcinoma (SCC)VII‐bearing mice, Masunaga et al also showed that methenamine enhanced the antitumor efficacy of cisplatin greater than the hypoxic sensitizer, tirapazamine . In regard to total tumour cell cytocidal effects, including elimination of quiescent cells, combining methenamine with radiotherapy or cisplatin demonstrated promising therapeutic potential, especially when methenamine was administered continuously . In subsequent studies, Masunaga et al subcutaneously injected mutantor empty vector transfected human head and neck squamous carcinoma cells into the hind legs of nude mice.…”
Section: Methenamine Synergism With Cisplatin and Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…In squamous cell carcinoma (SCC)VII‐bearing mice, Masunaga et al also showed that methenamine enhanced the antitumor efficacy of cisplatin greater than the hypoxic sensitizer, tirapazamine . In regard to total tumour cell cytocidal effects, including elimination of quiescent cells, combining methenamine with radiotherapy or cisplatin demonstrated promising therapeutic potential, especially when methenamine was administered continuously . In subsequent studies, Masunaga et al subcutaneously injected mutantor empty vector transfected human head and neck squamous carcinoma cells into the hind legs of nude mice.…”
Section: Methenamine Synergism With Cisplatin and Radiationmentioning
confidence: 99%
“…Hyperthermia is a heat‐treatment modality that targets malignant cells or their microenvironment; it is generally assumed that significant cancer cell death could be induced if malignant tissues were heated to over 42°C for 1 hour or longer . It is also presumed that hyperthermia would induce radiation and chemotherapy sensitization, partly through inhibition of the DNA damage repair machinery . For cancer treatment protocols, standard whole body hyperthermia (WBH) systemic temperatures of 41–42°C can be obtained and sustained for 60–120 minutes .…”
Section: Methenamine Synergism With Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation